Imaginator: A Proof‐of‐Concept Feasibility Trial of a Brief Imagery‐Based Psychological Intervention for Young People Who Self‐Harm. Issue 3 (14th February 2020) - Di Simplicio, Martina; Appiah‐Kusi, Elizabeth; Wilkinson, Paul; Watson, Peter; Meiser‐Stedman, Caroline; Kavanagh, David J.; Holmes, Emily A.
Abstract : Objectives: The Imaginator study tested the feasibility of a short mental imagery‐based psychological intervention for young people who self‐harm and used a stepped‐wedge design to investigate effects on self‐harm frequency reduction at 3 and 6 months. Method: A total of 38 participants aged 16–25 were recruited via community self‐referral and mental health services. Participants were randomized to immediate delivery of Functional Imagery Training (FIT) or usual care followed by delayed delivery after 3 months. FIT comprised two face‐to‐face sessions, five phone sessions, and use of a smartphone app. Outcomes' assessment was blind to allocation. Results: Three quarters of those who began treatment completed face‐to‐face sessions, and 57% completed five or more sessions in total. Self‐harm frequency data were obtained on 76% of the sample at 3 months (primary outcome) and 63% at 6 months. FIT produced moderate reductions in self‐harm frequency at 3 months after immediate ( d  = 0.65) and delayed delivery ( d  = 0.75). The Immediate FIT group maintained improvements from 3 to 6 months ( d  = 0.05). Participants receiving usual care also reduced self‐harm ( d  = 0.47). Conclusions: A brief mental imagery‐based psychological intervention targeting self‐harm in young people is feasible and may comprise a novel transdiagnostic treatment for self‐harm.